Intrinsic subtype and immunity score in identification of triple-negative breast cancer at low risk - Xinyu Ren; Tong Zhou; Yu Song; Huanwen Wu; Jeff Chou; Lance D. Miller; Zhiyong Liang; Songjie Shen (Breast)
Introduction: Triple-negative breast cancer (TNBC) is group of heterogeneity caner. Despite majority of them had the unfavorable prognosis, a subset of patients who do not receive chemotherapy exhibit a good prognosis. Biomarkers are required to recognize these group of pateints and improve the current therapeutic strategies for them. Methods: A retrospective analysis of 997 patients with TNBC from three datasets including 188 case of Peking Union Medical College Hospital (PUMCH) and two TNBC datasets from published cohort studies(279 case of Affy-set, 530 case of GSE set) was conducted. Intrinsic subtypes (basal-like, immune-enhanced, human epidermal growth factor receptor-2 [HER2]-enriched and luminal A/B) and tumor environmental immunity were evaluated using expression profiles of a 72-gene panel. Association of intrinsic subtype and immunity score with distant metastasis-free survival (DMFS) and overall survival (OS) was analyzed. Results: Five intrinsic subtypes were identified in the patients with TNBC, comprising 64 % basal-like, 19 % immune-enhanced, 11 % HER2-enriched, 5 % luminal A, and 2 % luminal B. In the absence of adjuvant chemotherapy (ACT), Luminal A and immune-enhanced subtypes showed better DMFS than basal-like, HER2-enriched, and luminal B subtypes(P = 0.35). Significantly good OS was observed in luminal A and immune-enhanced subtypes compared to basal-like and HER2-enriched subtypes (P < 0.05). So two subtype groups were further classified as low-risk subtypes, including luminal A and immune-enhanced, and high-risk subtypes, including basal-like, HER2-enriched, and luminal B. Except for the immune-enhanced subtype, each subtype was further sorted and grouped according to immunity score, istrong and iweak. Significant improvements in both DMFS and OS were observed in patients with istrong compared with those with iweak(P = 0.01 and 0.0051 respectively). When combining intrinsic subtype and immunity status to predict the benefit from ACT, all high-risk subtype patients demonstrated improved DMFS(P = 0.075) and OS(P < 0.0001), with istrong patients exhibiting greater benefit; low-risk subtype plus iweak patients showed marginal benefit, whereas low-risk subtype plus istrong patients demonstrated least benefit from ACT. Conclusion: Intrinsic subtype and immunity score is good prognostic biomarkers for patients with TNBC in the absence of chemotherapy. Combined intrinsic subtype and immunity evaluation could identify patients with TNBC who do not benefit from chemotherapy.